The Effectiveness of Mindfulness-integrated Cognitive Behavioral Therapy (MiCBT), Meta-Cognitive Therapy (MCT), Acceptance and Commitment Therapy (ACT), and Cognitive Behavioral Therapy (CBT) on Obsessive-compulsive disorder (OCD) - Derakhtkar , Ali; Khezrimoghadam, Noshirvan; Fazilatpour , Masoud (Shahroud Journal of Medical Sciences, 2021)
Background: Due to the lack of a comparative study on the effectiveness of cognitive-behavioral approaches on Obsessive-compulsive disorder (OCD), this study aimed to compare the effectiveness of CBT, ACT, MCT, and MICBT on the symptoms of OCD patients.Methods: The research design was experimental, with pre-test, post-test, follow-up, and a control group. The research population comprised patients with OCD who are referred to Shiraz (Iran) Counseling centers in the first quarter of 2017 with a definitive diagnosis of OCD. Participants were elected and had been assigned to five groups of twenty individuals by random. The subjects have been evaluated before and after the intervention by the Yale-Brown questionnaire. Data are analyzed using repeated measure analysis of Anova via SPSS 21.Results: The findings showed that all four types of intervention, i.e., MiCBT, MCT, ACT, and CBT, were effective in improving short-term OCD symptoms. Also, there was no significant difference in the long-term (follow-up/one month) between the MCT and CBT approaches; while ACT and MiCBT have maintained their therapeutic effect in the follow-up.Conclusions: OCD can be treated with all the mentioned therapies in short term; but, only ACT and MiCBT can be helpful in the long term.Keywords: Obsessive-Compulsive Disorder (OCD), Cognitive Behavioral Therapy (CBT), Acceptance and Commitment Therapy (ACT), Meta-Cognitive Therapy (MCT), Mindfulness-integrated Cognitive Behavioral Therapy (MiCBT).